Values of Happiness Toward an Anthropology of Purpose in Life - Kavedžija, Iza (HAU Books, 2016)
How people conceive of happiness reveals much about who they are and the values they hold dear. Drawing on ethnographic insights from diverse field sites around the world, this book offers a unique window onto the ways in which people grapple with fundamental questions about how to live and what it means to be human. Developing a distinctly anthropological approach concerned less with gauging how happy people are than with how happiness figures as an idea, mood, and motive in everyday life, the book explores how people strive to live well within challenging or even hostile circumstances. The contributors explore how happiness intersects with dominant social values as well as an array of aims and aspirations that are potentially conflicting, demonstrating that not every kind of happiness is seen as a worthwhile aim or evaluated in positive moral terms.